Data Analysis Services (MENA Report, 2015)
Subject of the framework agreement is the search engine optimization (SEO) and Marketing (SEA) for the websites relating to drug prevention. The project to be awarded covers the work involved in search engine marketing, maintenance and controlling of paid listings (Google AdWords) and the ongoing (editorial) Search Engine Optimization. The care includes, among other things, a display development, ad optimization, the ongoing campaign monitoring and controlling (reporting and measures derivation).